Varicella Zoster Virus in the Nervous System [version 1; referees: 3 approved] - Don Gilden (F1000Research, 2015)
Varicella zoster virus (VZV) is a ubiquitous, exclusively human alphaherpesvirus. Primary infection usually results in varicella (chickenpox), after which VZV becomes latent in ganglionic neurons along the entire neuraxis. As VZV-specific cell-mediated immunity declines in elderly and immunocompromised individuals, VZV reactivates and causes herpes zoster (shingles), frequently complicated by postherpetic neuralgia. VZV reactivation also produces multiple serious neurological and ocular diseases, such as cranial nerve palsies, meningoencephalitis, myelopathy, and VZV vasculopathy, including giant cell arteritis, with or without associated rash. Herein, we review the clinical, laboratory, imaging, and pathological features of neurological complications of VZV reactivation as well as diagnostic tests to verify VZV infection of the nervous system. Updates on the physical state of VZV DNA and viral gene expression in latently infected ganglia, neuronal, and primate models to study varicella pathogenesis and immunity are presented along with innovations in the immunization of elderly individuals to prevent VZV reactivation.